2012
DOI: 10.5194/bg-9-4787-2012
|View full text |Cite
|
Sign up to set email alerts
|

Intense photooxidative degradation of planktonic and bacterial lipids in sinking particles collected with sediment traps across the Canadian Beaufort Shelf (Arctic Ocean)

Abstract: Abstract. The lipid content of seven samples of sinking particles collected with sediment traps moored at ∼ 100 m depth in summer and fall across the Canadian Beaufort Shelf (Arctic Ocean) was investigated. Our main goal was to quantify and characterize the biotic and abiotic degradation processes that acted on sinking material during these periods. Diatoms, which dominated the phytoplanktonic assemblage in every trap sample, appeared to be remarkably sensitive to Type II (i.e. involving singlet oxygen) photod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 77 publications
(82 reference statements)
7
43
0
Order By: Relevance
“…Singlet oxygen transfer from the phytodetritus to attached heterotrophic bacteria could induce strong oxidative damage in these organisms (not only on unsaturated fatty acids but also on proteins and nucleic acids [57,58]), which has the potential to limit their growth and therefore contribute to a better preservation of algal organic matter during the sedimentation. Note that the surprising recalcitrance of phytodetritus towards biodegradation processes observed during the Arctic midnight sun period was recently attributed to the strong photodegradation state of heterotrophic bacteria associated with this material [33], which likely resulted from the efficient transfer of singlet oxygen from the photodegraded phytoplanktonic cells to the attached bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singlet oxygen transfer from the phytodetritus to attached heterotrophic bacteria could induce strong oxidative damage in these organisms (not only on unsaturated fatty acids but also on proteins and nucleic acids [57,58]), which has the potential to limit their growth and therefore contribute to a better preservation of algal organic matter during the sedimentation. Note that the surprising recalcitrance of phytodetritus towards biodegradation processes observed during the Arctic midnight sun period was recently attributed to the strong photodegradation state of heterotrophic bacteria associated with this material [33], which likely resulted from the efficient transfer of singlet oxygen from the photodegraded phytoplanktonic cells to the attached bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The present study focuses on the effects of a natural source of 1 O 2 (senescent phytoplanktonic cells) to their attached bacteria. These processes, which have been ignored in the literature until now, might strongly limit bacterial growth in the seawater column and, consequently, contribute to a better preservation of algal material toward biotic degradation during settling [33]. …”
Section: Introductionmentioning
confidence: 99%
“…While we did not observe statistically significant rates of photooxidation in monounsaturated IP-DAG, a significant body of literature has shown that MUFA-derived oxylipins (i.e., free fatty acid derivatives cleaved from their lipid headgroup) do contribute to the oxidized lipid pool in surface waters, sinking particles, and seafloor marine sediments on scales which are all environmentally relevant (Marchand and Rontani, 2001;Rontani, 1999;Rontani et al, 2016;Rontani et al, 2012a;Rontani et al, 2012b). In Antarctic waters specifically, there is reason to presume that oxidation and removal of certain lipids at the ocean's surface could affect the quality of the lipid biomass that is exported to depth.…”
Section: Conclusion and Additional Biogeochemical Implicationsmentioning
confidence: 63%
“…While lipid peroxidation has been implicated in studies of UVR stress in Antarctic organisms and ecosystems, it has to our knowledge never been characterized at the molecular level, nor its significance explored at the ecosystem scale in the Antarctic. Groundbreaking work by Rontani and others (Christodoulou et al, 2010;Marchand and Rontani, 2001;Rontani, 1999;2001;Rontani et al, 1998;Rontani et al, 2016;Rontani et al, 2012a;Rontani et al, 2012b) has established that the photooxidation of mono-and di-unsaturated fatty acids in surface ocean biomass is a process significant enough to be detected via certain short-chain oxylipin biomarkers in sinking marine particulate material. Rontani and others have used these biomarkers to make estimates of the overall photooxidation state of the organic matter present in these particles, but there are virtually no estimates at the ecosystem scale of the rate at which organic matter in the surface ocean can be degraded via lipid photooxidation compared with many other processes that contribute to remineralization.…”
Section: Uvr-induced Oxylipin Production Via Ros Has Been Extensivelymentioning
confidence: 99%
“…These authors suggested that extracellular H 2 O 2 could be a common byproduct of biological processes (as is intracellular H 2 O 2 ), or a product of a specific biochemical process, indicating that H 2 O 2 production rates might vary with environmental factors and species composition. Interestingly, it was recently hypothesized that abiotic processes such as photoxidation are able to produce peroxides (i.e., hydroperoxides associated with organic matter) that might inhibit bacterial activity by singlet oxygen transfer from phytodetritus to particle-attached bacteria [15]. The oxidative stress provoked by such particle-associated production of reactive oxygen species could be particularly relevant in microhabitats and in the deep ocean due to the preferential particle-related life strategy of dark ocean prokaryotes [16], [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%